(untitled) (Olhar de Professor, 2025)
This article presents an experience report of an extension course in Libras offered in the first semester of 2024 by the Federal University of Campina Grande. The aim was to discuss the training course on the deaf and Libras to support the practices of teachers and civil servants at the university. The methodology included a bibliographical survey of a narrative review of the literature, followed by documentary data from the teacher’s records, notices and didactic instruments used by her during the course, such as the teacher’s evaluation and records. The data was analyzed using a qualitative approach, based on interpreting phenomena without quantifying them. As such, the course enabled the participants to get involved in the proposed activities, and the students ended up with significant knowledge about sign language and deaf people.